1999
DOI: 10.1046/j.1440-1819.1999.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnographic and urodynamic changes in a case of obstructive sleep apnea syndrome with enuresis

Abstract: A 53-year-old female patient with obstructive sleep apnea syndrome was reported. She had complained of enuresis as well as a 15-year history of snoring, but she had no complaint of sleep and awake disturbance. Polysomnographic study showed repeated obstructive apnea and hypopnea with an apnea/hypopnea index of 52.6, and severe oxygen desaturation during sleep. On cystometography during sleep, the changing amplitude of the spike wave corresponds to the changes of respiratory efforts against a closed upper airwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…Several different pathophysiologic mechanisms have been proposed to explain the association between the two conditions. An increase in intra-abdominal pressure caused by intense inspiratory efforts against a closed upper airway has been implicated in the pathogenesis of enuresis (19). In addition, we have previously shown that fractional urinary excretion of sodium increases in parallel with severity of SDB and diastolic blood pressure in children with snoring (20).…”
Section: Discussionmentioning
confidence: 87%
“…Several different pathophysiologic mechanisms have been proposed to explain the association between the two conditions. An increase in intra-abdominal pressure caused by intense inspiratory efforts against a closed upper airway has been implicated in the pathogenesis of enuresis (19). In addition, we have previously shown that fractional urinary excretion of sodium increases in parallel with severity of SDB and diastolic blood pressure in children with snoring (20).…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, increased intra-abdominal pressure generated during apneic events may be transmitted to the bladder increasing detrussor pressure on cystometrogram. 20 The relationship between the increased detrussor pressure during an apneic episode and nocturia needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive episodes of hypoxia during apnea and alterations in intrapleural negative pressure will affect the right atrium, resulting in increased atrial natriuretic peptide (ANP) secretion. Increased levels of ANP will result in inhibition of the renin-angiotensin-aldosterone system, eventually causing increased sodium and urine excretion (21)(22)(23). Furthermore, increased sympathetic activity in OSA patients causes increased urine production and hyperactivity of bladder smooth musculature (10).…”
Section: Discussionmentioning
confidence: 99%